Pengaruh Prinsip-Prinsip Good Governance Terhadap Tingkat Kesehatan LPD Pada LPD Se-Kecamatan Abiansemal - Madani Hapsari, Ni Made; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p03, 2018)
Good Governance is governance that consists of transparency, accountability, responsibility, independence, and fairness in an effort to improve company performance. The purpose of this study to determine the effect of transparency, accountability, responsibility, independence and fairness on the health level of LPD. This research was conducted in all LPDs in Abiansemal District. The number of samples taken was 34 chairmen of LPD, with probability sampling method. Data collection is done through interviews, observation and documentation. The analysis technique used is Multiple Liniear Regression Analysis. Found that only transparency has a significant effect on the health level of LPD, while other factors such as accountability, responsiveness, independence and fairness have no significant effect on the health level of LPDs. This shows when transparency is the focus of management's attention, accountability, responsibility, independence and fairness are seen as something that must be applied by LPDs management. Keywords: good governance, healht level of LPD